The Role of parents in Online Learning Assistance for Elementary School Students - Azolla Afifah Kusuma Wardani; Ika Candra Sayekti (State Islamic University of Raden Fatah Palembang, South Sumatra, Indonesia, 2022)
This research was aimed to explore the role of parents in online learning assistance, identify problems parents encounter, and find a solution. The method used in this research was descriptive qualitative method and case study design. Data collection techniques were conducted by interview, observation, and documentation. The data validity of this research was a triangulation of sources and techniques. The research data analysis technique used interactive analysis; they were data reduction, data presentation, and drawing conclusions. The location of this research was conducted at Public Elementary School of 01 Girilayu. The results of this study were: 1) most of the respondents' parents have carried out their roles as educators, mentors, motivators, and facilitators; 2) the problems faced by parents come from the parents themselves, students, and the environment; 3) most of the parents can overcome the existing problems, even though, a small number of parent respondents are indifferent to the existing problems. The implication could be concluded that the maximum role of parents in online learning assistance will make student learning at home fun and achieve the desired goals.